2010
DOI: 10.1105/tpc.110.077461
|View full text |Cite
|
Sign up to set email alerts
|

RanGAP2 Mediates Nucleocytoplasmic Partitioning of the NB-LRR Immune Receptor Rx in the Solanaceae, Thereby Dictating Rx Function  

Abstract: The potato (Solanum tuberosum) nucleotide binding-leucine-rich repeat immune receptor Rx confers resistance to Potato virus X (PVX) and requires Ran GTPase-activating protein 2 (RanGAP2) for effective immune signaling. Although Rx does not contain a discernible nuclear localization signal, the protein localizes to both the cytoplasm and nucleus in Nicotiana benthamiana. Transient coexpression of Rx and cytoplasmically localized RanGAP2 sequesters Rx in the cytoplasm. This relocation of the immune receptor appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 101 publications
4
153
0
2
Order By: Relevance
“…In terms of compartment-dependent activation, Sr33 is more similar to the potato CC-NLR Rx, a nucleo-cytoplasmic protein that recognizes the potato virus X (PVX) coat protein (CP) (32,49). Rx interacts with the small cytosolic GTPase RanGAP2, which is required for Rx function (50,51) and affects Rx nucleocytoplasmic distribution (49).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of compartment-dependent activation, Sr33 is more similar to the potato CC-NLR Rx, a nucleo-cytoplasmic protein that recognizes the potato virus X (PVX) coat protein (CP) (32,49). Rx interacts with the small cytosolic GTPase RanGAP2, which is required for Rx function (50,51) and affects Rx nucleocytoplasmic distribution (49).…”
Section: Discussionmentioning
confidence: 99%
“…This system has been widely used for the functional analysis of HR mediated by NLRs from both monocots and dicots (Leister et al, 2005;van Ooijen et al, 2008;Slootweg et al, 2010;Tameling et al, 2010;Bai et al, 2012;Qi et al, 2012). We have recently shown that this is an appropriate system for the functional analysis of HR modulated by Rp1-D21 and its regulators (Wang and Balint-Kurti, 2015;Wang et al, 2015cWang et al, , 2015d.…”
Section: Ccoaomt2mentioning
confidence: 99%
“…However, no evidence exists that RanGAPs themselves can shuttle proteins from the cytoplasm to the nucleus; therefore, it is not likely that RanGAP2 has a direct role in the transport of Rx1 to the nucleus. On the other hand, a detailed study on the effect RanGAP2 has on the subcellular localization and activation of Rx1 (Tameling et al, 2010) showed that RanGAP2 affects the nucleocytoplasmic partitioning of Rx1 but does not require GAP (GTPase activating protein) activity to produce this effect.…”
Section: The CC and Lrr Domains Play Distinct Roles In The Nucleocytomentioning
confidence: 99%
“…If this is true, and a similar indirect RanGAP2-mediated recognition underlies PVX CP recognition, then this would explain why the nuclear-targeted PVX CP no longer activates Rx1. However, a study by Tameling et al (2010) determining the link between RanGAP2 localization and Rx1 functioning demonstrated that when the RanGAP2 WPP domain itself is targeted to the nucleus by an NLS fusion, thereby pulling Rx1 into the nucleus as well, it still does not allow Rx1 activation in the nuclear compartment. However, it might be the full-length RanGAP2 that is required for elicitor recognition.…”
Section: Rx1 Is Activated In the Cytoplasmic Compartmentmentioning
confidence: 99%